Double Bagged or Fries With That: Adolescents’ Perceptions of the Job Market in Four Urban Vancouver Secondary Schools - Benjamin, Amanda (Alberta Journal of Educational Research, 2010)
This article critically examines adolescents’ perceptions of the job market in Vancouver, British Columbia. Employing document analysis, interviews with teachers and students, and classroom observations, the article explores how adolescents in four urban schools understood the difference between having a job and a career in the context of the Career and Personal Planning Curriculum (CAPP). In taking a discourse-oriented approach, this study reveals an important social class distinction in how students conceptualized what it meant to have a job and pointed to how career education influenced their perceptions about jobs.